Fever and Pancytopenia in a Liver Transplant Recipient: Going Against the Rules of Occam's Razor. Issue 7 (July 2017) - Lum, Lionel Hon Wai; Chen, Fei Wen; Jackett, Louise; Strasser, Simone I.; Davis, Rebecca J.
Abstract : Abstract: The syndrome of fever and pancytopenia is not infrequently encountered postliver transplant, and a broad differential list of infectious and noninfectious aetiologies can be invoked. A transplant patient is susceptible to more than 1 opportunistic infection or disease process. We described the diagnostic conundrums in managing our patient who ran a complex protracted course postliver transplant. He was diagnosed to have both disseminated tuberculosis and graft-versus-host disease, a rare complication after solid organ transplantation.